Skepticism, Modernity and Critical Theory - Walsh, P. author. aut Link
XII, 182 p.
Keywords: This book examines the issue of philosophical skepticism in the light of its relevance for the critique of modernity associated with the Frankfurt School. It situates the problem of skepticism in the context of the history of philosophy and explores its significance for the modern crisis of reason manifested in post-Kantian philosophy, which presaged the critical turn toward social theory.